Baltic Archaeology, Cultural History, Ancient Lithuanian Symbolism, Old Europe, and the Archaeomythology of Marija Gimbutas - Marler, Joan (Archaeologia Lituana, 2022)
Marija Alseikaitė-Gimbutienė (Gimbutas) (1921–1994) was born and raised in Lithuania within a family of physicians and intellectuals devoted to the preservation of Lithuanian folk culture. She studied archaeology with Professor Jonas Puzinas who was the first scientifically trained archaeologist in independent Lithuania. Marija Gimbutas was thoroughly trained in Eastern European archaeology, Baltic prehistory, Indo-European linguistics, ethnology, history, folklore, mythology, and European languages taught by the most accomplished Lithuanian scholars in their fields. In 1942 she earned a Master՚s degree at Vilnius University for her thesis on “Burial Practices in the Lithuanian Iron Age.” In 1946 she earned her doctorate in archaeology from Tübingen University in Germany before immigrating to the United States in 1949. This paper traces her prodigious production of major publications and scholarly achievements fostered by her multidisciplinary education in Lithuania. It discusses the development of her Kurgan hypothesis, her excavations in Southeastern Europe, her theory of Old Europe, her formulation of archaeomythology, and the ancient veneration of the earth as the source of life.
Keywords: Marija Gimbutas; Jonas Puzinas; The Balts; Old Europe; archaeomythology